Birth weight and long-term risk of mortality among US men and women: Results from three prospective cohort studies - Yi-Xin Wang; Ming Ding; Yanping Li; Liang Wang; Janet W. Rich-Edwards; Andrea A. Florio; JoAnn E. Manson; Jorge E. Chavarro (Elsevier, 2022)
Summary: Background: Weight at birth has been associated with the development of various adult diseases, but its association with mortality remains unclear. Methods: We included 22,389 men from the Health Professionals Follow-up Study (1994-2018) and 162,231 women from the Nurses' Health Study (1992-2018) and the Nurses' Health Study II (1991-2019). The hazard ratios (HRs) of mortality according to birth weight were estimated by Cox proportional hazards regression models with adjustment for potential confounders. Findings: Compared to women reporting a birth weight of 3.16-3.82 kg, the pooled HRs for all-cause mortality were 1.13 (95% CI, 1.08 to 1.17), 0.99 (95% CI, 0.96 to 1.02), 1.04 (95% CI, 1.00 to 1.08), and 1.03 (95% CI, 0.96 to 1.10), respectively, for women with a birth weight of <2.5, 2.5-3.15, 3.83-4.5, and >4.5 kg. In cause-specific mortality analyses, women reporting birth weight >4.5 kg had a higher risk of cancer mortality (HR=1.15, 95% CI: 1.00 to 1.31), whereas women with a birth weight <2.5 kg had an elevated risk of mortality from cardiovascular diseases (HR=1.15; 95% CI, 1.05 to 1.25) and respiratory diseases (HR=1.35; 95% CI, 1.18 to 1.54). Birth weight was unrelated to all-cause mortality among men, but cause-specific mortality analyses showed an inverse association with cardiovascular disease mortality and a positive association with cancer mortality (p for linear trend = 0.012 and 0.0039, respectively). Interpretation: low birth weight was associated with a greater risk of cardiovascular and respiratory disease mortality among women, while large birth weight was associated with a greater cancer mortality risk in both men and women. Funding: The National Institutes of Health grants U01-HL145386, U01-CA176726, R01-HL034594, R01-HL088521, UM-CA186107, P01-CA87969, R01-CA49449, R01-CA67262, U01-HL145386, U01-CA167552, R01-HL35464, and R24-ES028521-01 support this study.